Socioeconomic Determinants of Diet Quality on Overweight and Obesity in Adults Aged 40–59 Years in Inner Mongolia: A Cross-Sectional Study - Su, Yuenan; Du, Sha; Yang, Min; Wu, Jing; Lu, Haiwen; Wang, Xuemei (International Journal of Public Health, 2021)
Objectives:This study investigated the relationship of socioeconomic status(SES),dietary quality and overweight and obesity in adults aged 40-59 years in Inner Mongolia. Methods:This cross-sectional study was based on the survey of Chronic Disease and Nutrition Monitoring in Adults in Inner Mongolia in 2015.Dietary quality was evaluated by the Alternate Mediterranean Diet score.SES was measured by household annual income.Multivariate logistic regression models and path analysis were performed to determine the association of SES,dietary quality and overweight and obesity. Results:Among participants,63.0% had overweight and obesity. In high SES group,66.4% had overweight and obesity. Higher SES was related to increased overweight and obesity risk(OR=1.351,95%CI:1.016-1.796). There was a positive correlation between SES and the intake of red and processed meat(r=0.132,P<0.05). Higher intake of red and processed meat was associated with lower dietary quality(β=-0.34). In turn,lower dietary quality was associated with higher risk of overweight and obesity(β=-0.10). Higher aMeds was related to lower risk of overweight and obesity(OR=0.560,95%CI:0.391-0.803). Conclusion:In Inner Mongolia,during the period of economic transition,people aged 40-59 years in high SES had a poor dietary quality,which was related to higher risk of overweight and obesity.